The Relationship between Premature Rupture of Membranes and the Level of Anxiety in Maternity Women at the Kumbe Community Health Center in 2023 - Eutalia Anitu; Anggrawati Wulandari; Riza Tsalatsatul Mufida; Eri Puji Kumalasari (Journal of Health Science Community, 2024)
Premature rupture of membranes is a condition where the amniotic sac ruptures early before delivery or when the gestational age has not reached 37 weeks. The aim of this study was to determine the relationship between the incidence of premature rupture of membranes and the level of anxiety among mothers giving birth in the Kumbe Community Health Center working area in 2023. The design of this study was correlational analysis with a cross-sectional time approach. The sample in this study was 30 pregnant women approaching delivery in the Kumbe Community Health Center Working Area, Merauke Regency. The sampling method uses accidental sampling technique. Data collection uses questionnaires and observation sheets. It is known that out of 30 respondents, 12 respondents (42.0%) experienced mild anxiety, while respondents (64.0%) experienced premature rupture of membranes. The results of statistical tests with Chi Square show a significance level of 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, thus there is a relationship between anxiety during pregnancy and the relationship between the incidence of premature rupture of membranes and the level of anxiety in mothers giving birth in the Kumbe Health Center working area in 2023.